The theory of the three-dimensional spiral of sense: an application with special reference to identity and professionalisation in other disciplinary areas - Aparicio, Miriam Teresita (2015)
This article presents the development of a new theory called “Towards a Systemic Sui Generis Paradigm: The Theory of the Three Dimensional Spiral of Sense” Applied to Identity and Professionalization” (Article 2). This second part deals with the remaining four disciplinary areas, in which the new analysis of the social data was carried out: Education, Health, Science, Media, International Relations and Interculturality. Different research works – national and international – are presented for each area, and in turn, the theoretical frame, objectives, hypothesis/questions, variables/dimensions, material and methods, results and discussion are shown briefly for each case. Then, there is the general interpretation of results and a conclusion, from which the mainstays of this research, based on reference research works, arise; the research which is the base of out theory. It should be pointed out that, among the selected reference research works, some are comparative studies with European countries, others with Latin-American countries. The methodology used was quantitative (statistical analysis, a semi-structured survey) but mainly qualitative (lexicometric analysis, hierarchical evocations, interviews). The approach was macro-micro-meso-macro, micro, macro It consists of a kind of sui generis systemicism which recovers interactions between individuals, organizations/institutions and macro contexts. Such interplay does not overlook the individuals nor the contexts. In consists of a comprehensive, holistic approach of the complexity, even though it lies on different anthropological bases. This approach stands aside from any kind of reductionist determinisms. The results, particularly the qualitative ones, show the rich interactions underlying the continuance or innovation processes, which favor or hinder the individuals’, countries’ and institutions’ development, as well as their identity/identities in times of abrupt change. At the same time, these results reveal the need for Professionalization in relation to personal fulfillment, employability and macro social development.